Scientific Journey Through Borneo: Loagan Bunut: a Scientific Expedition on the Physical, Chemical, Biological, and Sociological Aspects - Andrew Alek, Tuen (Ministry of Natural Resources and Environment, 2006)
This book reports the findings of the Loagan Bunut Scientific Expedition 2004. The aim of the expedition is to study and document the physical, biological and socio-economic aspects of the Loagan Bunut National Park as well as the ecological processes. It contains twenty seven papers presented during a seminar in Kuching on 2-3 August 2004 during which the findings of the expedition were presented were presented and discussed in detail.